Clinical integration of patient-reported outcome measures to enhance the care of patients with SLE: a multi-centre prospective cohort study. (31st March 2022) - Kasturi, Shanthini; Price, Lori Lyn; LeClair, Amy; Patel, Neena; Shetty, Shreya; Sheira, Dina; Weber, Serena; Curtis, David; Nowell, W Benjamin; Salmon, Jane; Terrin, Norma; McAlindon, Timothy E; et al.
Abstract: Objective: To assess the feasibility and impact of integrating electronic patient-reported outcome measures (PROMs) into the routine outpatient care of patients with SLE. Methods: We conducted a prospective cohort study, utilizing a mixed-methods sequential explanatory design, of SLE outpatients receiving rheumatology care at two academic medical centres. Participants completed electronic PROMs at enrolment and then prior to their next two routine rheumatology visits. PROM score reports were shared with patients and rheumatologists before visits. Patients and rheumatologists completed post-visit surveys evaluating the utility of PROMs in the clinical encounters. Focus groups of patients and interviews with treating rheumatologists were conducted to further explore their experience utilizing PROMs. Results: A total of 105 SLE patients and 17 rheumatologists participated in the study. Patients completed PROMs in 159 of 184 encounters (86%), with 93% of surveys completed remotely. Patients reported that PROMs were 'quite a bit' or 'very' useful (55% of encounters) and beneficial to communication (55% of encounters). In contrast, physicians found PROMs useful (20%) and beneficial to communication (17%) less frequently. There was no significant change in visit length, health-related quality of life or disease activity after implementation of PROMs; however, patient satisfaction improved slightly. Qualitative analyses revealed that patients felt PROMs provided utility primarily by facilitating communication, particularly when physicians discussed the surveys. Conclusion: The remote capture and integration of electronic PROMs into clinical care was feasible in a diverse cohort of SLE outpatients. PROMs were useful to patients and enhanced their clinical experience primarily by facilitating communication.